Oxidative Stress Induced Thrombosis and Hypercholesterolemic Condition in COVID-19 Infection - Ashfaq Ahmed; Hrishik Iqbal; Md Shaki Mostaid; Afroza Zannat; Srikumar Chakravarthi; Nikolaos Syrmos (Journal of Current Health Sciences, 2026)
The COVID-19 pandemic, caused by SARS-CoV-2, has emerged as a global health crisis, with severe disease and mortality disproportionately affecting individuals with comorbidities such as cardiovascular disease, diabetes, obesity, and immunosuppression. These conditions are associated with elevated basal reactive oxygen species (ROS) levels, predisposing patients to oxidative stress, systemic inflammation, endothelial dysfunction, and thrombotic complications. SARS-CoV-2 infection further exacerbates ROS generation via dysregulation of the renin–angiotensin system, NADPH oxidase activation, and immune-mediated neutrophil and macrophage responses, contributing to vascular injury, cytokine storm, and acute respiratory distress syndrome (ARDS). Hypercholesterolemic patients are particularly vulnerable, as oxidized LDL (OxLDL) enhances ROS production, promotes neutrophil extracellular trap formation, and accelerates thrombosis, further compounding COVID-19 severity. COVID-19–associated coagulopathy is characterized by elevated D-dimer, von Willebrand factor, and platelet activation, reflecting systemic hypercoagulability and multiorgan involvement. Therapeutically, targeting oxidative stress represents a promising strategy. Statins exhibit cholesterol-lowering and immunomodulatory effects, potentially reducing thrombotic risk. Nrf2 activators, glutathione, and N-acetylcysteine enhance endogenous antioxidant defenses, mitigate inflammation, and preserve endothelial integrity. Micronutrients such as vitamins C, D, E, and selenium further support redox homeostasis and immune function. Collectively, in this narrative review we have shown that understanding the interplay between oxidative stress, thrombosis, hypercholesterolemia, and immune dysregulation may inform preventive and therapeutic strategies to improve outcomes in high-risk COVID-19 patients. Clinical trials are warranted to validate the efficacy of these interventions.